2014
DOI: 10.1210/en.2013-2180
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Defines the Regulation of Postnatal Cardiac Growth by 17β-Estradiol Through a β-Catenin Mechanism

Abstract: Estrogen regulates several biological processes in health and disease. Specifically, estrogen exerts antihypertrophic effects in the diseased heart. However, its role in the healthy heart remains elusive. Our initial aim was to identify the effects of 17β-estradiol (E2) on cardiac morphology and global gene expression in the healthy mouse heart. Two-month-old C57BL/6J mice were ovariectomized and treated with E2 or vehicle for 3 months. We report that E2 induced physiological hypertrophic growth in the healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Such an acute response suggests that a nongenomic mechanism of kinase activation by E 2 may be involved. However, in some circumstances, signaling pathways for genomic and nongenomic actions of E 2 on target genes can interact (4), and E 2 has been shown to influence the expression of several members of the contractile apparatus in the heart, including myosin heavy chain, via direct gene regulation (25,26). Therefore, genomic mechanisms should not at this point be excluded, and additional studies are necessary to distinguish genomic vs. nongenomic ER mechanisms of kinase activation in skeletal muscle fibers in relation to phosphorylation of the RLC.…”
Section: Discussionmentioning
confidence: 99%
“…Such an acute response suggests that a nongenomic mechanism of kinase activation by E 2 may be involved. However, in some circumstances, signaling pathways for genomic and nongenomic actions of E 2 on target genes can interact (4), and E 2 has been shown to influence the expression of several members of the contractile apparatus in the heart, including myosin heavy chain, via direct gene regulation (25,26). Therefore, genomic mechanisms should not at this point be excluded, and additional studies are necessary to distinguish genomic vs. nongenomic ER mechanisms of kinase activation in skeletal muscle fibers in relation to phosphorylation of the RLC.…”
Section: Discussionmentioning
confidence: 99%
“…The computational and statistical analysis of the microarray data was carried out using the R version 2.14.2 software 16 and the Bioconductor packages, 17 as described recently. 18,19 Following background correction, expression data were normalized with the variance stabilization and normalization algorithm, 20 and log 2 transformed using the median polish algorithm of robust multiarray average. 21 The quality of the data was assessed with the affy 22 and the arrayQualityMetrics 23 packages.…”
Section: Microarray Data Analysismentioning
confidence: 99%
“…A recent sequence comparison of B6J and B6N from Taconic Farms showed that these sub-strains differ only in 34 single nucleotide polymorphisms, 2 indels in coding regions and 15 structural gene variants. Despite their genetic similarity, both sub-strains differ in a number of phenotypes including behaviors (Bechard et al 2012;Blum et al 1982;Bothe et al 2004;Bryant et al 2008;Crusio et al 1991;Hager et al 2014;Kumar et al 2013;Matsuo et al 2010;Mogil & Wilson 1997;Mouri et al 2012;Mulligan et al 2008;Ramachandra et al 2007;Siegmund et al 2005;Simon et al 2013;Stiedl et al 1999), circadian rhythms (Banks et al 2014), metabolic functions and responses to high-fat diet (Andersson et al 2010;Heiker et al 2014;Podrini et al 2013;Simon et al 2013;Walker et al 2014), as well as the physiology and pathology of the cardiovascular (Cardin et al 2014;Kararigas et al 2014;Moreth et al 2014), visual (Mattapallil et al 2012;Simon et al 2013) and auditory systems (Kendall & Schacht 2014;Schnabolk et al 2014). These phenotype differences are important, because many studies use genetic mouse models on these two C57BL/6 genetic backgrounds.…”
mentioning
confidence: 99%